Measurement of the Z/gamma* -> tau tau cross section in pp collisions at root s=13 TeV and validation of tau lepton analysis techniques - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer New York LLC, 2018)
A measurement is presented of the Z/γ ∗ → τ τ cross section in pp collisions at √s = 13 TeV, using data recorded by the CMS experiment at the LHC, corresponding to an integrated luminosity of 2.3 fb−1. The product of the inclusive cross section and branching fraction is measured to be σ (pp → Z/γ ∗+X) B(Z/γ ∗ → ττ) = 1848 ± 12 (stat) ± 67 (syst + lumi) pb, in agreement with the standard model expectation, computed at next-to-next-to-leading order accuracy in perturbative quantum chromodynamics. The measurement is used to validate new analysis techniques relevant for future measurements of τ lepton production. The measurement also provides the reconstruction efficiency and energy scale for τ decays to hadrons + ντ final states, determined with respective relative uncertainties of 2.2 and 0.9%